2013
DOI: 10.1111/1751-2980.12103
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of nonhuman primate embryonic stem cells into hepatocyte‐like cells

Abstract: With cytokine induction, rhesus monkey ESC differentiated into cells displaying morphological features, gene expression patterns and metabolic activities characteristic of hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A previous ultrastructural study of mESCs has shown that there is a clear increase in the cytoplasmic volume when ESCs are differentiated as EBs; in addition, there is an increase in protein synthesis (Sampath et al, 2008). In addition, many other investigations have studied ultrastructural morphology of EBs, which differentiated into various committed cell types, including cardiomyocytes (Taha et al, 2012), endothelial cells (Festag et al, 2007), hepatocytes (Kuai et al, 2014), skeletal muscle cells (Kawagoe et al, 2011), pancreatic exocrine enzyme-producing cells (Shirasawa et al, 2011), and renal cells (Kramer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A previous ultrastructural study of mESCs has shown that there is a clear increase in the cytoplasmic volume when ESCs are differentiated as EBs; in addition, there is an increase in protein synthesis (Sampath et al, 2008). In addition, many other investigations have studied ultrastructural morphology of EBs, which differentiated into various committed cell types, including cardiomyocytes (Taha et al, 2012), endothelial cells (Festag et al, 2007), hepatocytes (Kuai et al, 2014), skeletal muscle cells (Kawagoe et al, 2011), pancreatic exocrine enzyme-producing cells (Shirasawa et al, 2011), and renal cells (Kramer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Standard cryopreservation (FBS, 10% DMSO) of LIV0APOLY cells had no effect on the doubling time (or viability) of the cells; in contrast, primary hepatocytes are reported to be poorly resistant to cryopreservation, which affects cell viability, morphology, and functionality ( 21 ). We found that the LIV0APOLY cell line expressed defined hepatocyte markers, such as albumin and CK18 ( 22 , 26 , 32 , 54 ). Expression of albumin in two-dimensionally cultured primary hepatocytes has been shown to decrease after approximately 1 wk, whereas cultured LIV0APOLY cells retained high expression of albumin over 45 days and for at least 14 days following differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, these HLCs displayed specific characteristics that define a typical "hepatocyte", as determined by both qualitative assays and qualitative analysis. 50 Significantly, our hepatic differentiation protocol is distinct from that of other reports of non-human primates, namely rhesus macaque ESCs 42,43 and cynomolgus ESCs. 48,49 We have used a modified three-step procedure that was previously developed in our laboratory to differentiate porcine iPS cells into HLCs.…”
Section: Dovepressmentioning
confidence: 97%
“…Aravalli et al ESCs from human, rodent, porcine, and monkey species have been differentiated into HLCs. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] In this study, we have carried out hepatic differentiation of marmoset ESCs into HLCs and characterized them using a combination of immunohistochemistry, morphological analyses, RT-PCR, and biochemical assays. Activin A-treated marmoset ESCs and primary human hepatocytes (PHHs) were used as controls.…”
Section: Dovepressmentioning
confidence: 99%